Fire Safety Assessment of Building-Integrated Photovoltaics (BIPVs) - Ping Fang; Lihong Zhao; Guangheng Song; Jiaqi Dong; Jinlong Zhao; Zhenhua Wang (Fire, 2025)
Building-Integrated Photovoltaic (BIPV) systems, which seamlessly integrate solar photovoltaic components into building structures, have garnered widespread attention for their aesthetic appeal and energy efficiency. However, the promotion of BIPV systems has also raised new fire safety concerns. This paper reviews recent fire incident cases and conducts risk identification for factors such as building and environmental risks, photovoltaic systems, electrical equipment, and safety protection. A fire risk assessment is performed using the Analytic Hierarchy Process (AHP) to evaluate the overall fire safety of BIPV systems. Based on the assessment, corresponding safety design strategies are proposed to ensure the safety of buildings and occupants. The research results indicate that BIPV systems pose certain fire hazards, and that proper design and regulation are crucial to mitigate these risks.